PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 008 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Leni Marlina; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is in art of the science,s, studies students learning outcomes with an average grade 58,75. This researth is classroom action researth (CAR). That is suppose to increase the social studies students learning outcomes at fourth brrade of elementary school 008 Sungai Segajah Kubu in Rokan Hilir District. Formulation of this research is: Does the application of cooperative learning model pembelajaran langsung can increase the learning outcomes of science,s studies at fourth grade of elementary school 008 Sungai Segajah Kubu in Rokan Hilir district. The students learning outcomes before CAR is about 56,5% in fair category. Whereas after CAR in cycle 1 increase about 67,75% with fairly good category ard in cycle II is about 72% with good category the comparison of students learning outcomes in before and after CAR in cycle I inerease about 56,5% whereas from cycle 1 to cycle 2 incerease about 19,91 % and from leased scare to cycle 1 increase about 27,43% and from based secore to cycle increase about. The teacher is activity has an average incycle 1 is about 70%. Whereas in cycle 2 is about 85%. And the students activity have an average value in cycle 1 is about 65% and cycle 2 is about 80%. The result of this research is the application of cooperative learning model type pembelajaran langsung can increase the achievement studies students learning outcomes at fourth brade of elementary school 008 Sungai Segajah Kubu in Rokan Hilir District.Key Word : Kooperative type make a match, The science,s students achievement